The role of medial plantar nerve conduction studies in the diagnosis of diabetic polyneuropathy: A comparative analysis with sural nerve - Koç Yamanyar, Gülçin; Aslan, Hüsniye (The European Research Journal, 2025)
Objectives: Diabetic neuropathy, significantly impacts patients’ quality of life and may lead to severe morbidity in the long term. Early detection of diabetic neuropathy is crucial in preventing or delaying irreversible damage. In this study, we aimed to evaluate the role of medial plantar nerve conduction studies in the early diagnosis of diabetic polyneuropathy and to determine which of the examined nerve conduction studies demonstrates higher sensitivity. Methods: Sixty patients with suspected diabetic polyneuropathy and 30 healthy controls were included. Diabetic neuropathy symptoms were assessed using the Diabetic Neuropathy Symptom (DNS) score. Sensory and motor nerve conduction studies, including median, ulnar, posterior tibial, medial plantar, and sural nerves, were performed. Results: Sensory response amplitudes of both medial plantar and sural nerves were significantly lower in patients compared to controls. Abnormal sensory responses were detected in 23 (38.33%) patients for the sural nerve and 39 (65%) for the medial plantar nerve. Conclusions: Both nerve conduction studies are valuable in diagnosing diabetic polyneuropathy, but medial plantar nerve conduction studies demonstrated higher sensitivity. Including medial plantar nerve assessments in routine evaluations may improve diagnostic accuracy.